Hegemony comes from the factory: management, labourers and work organization in industrial production - Pinto, Geraldo Augusto (Universidade Estadual Paulista / UNESP, 2011)
It is not uncommon to find in the literature analyses that conceive Taylorism/Fordism as just a managment system of the labour power, which, incidentally, in this strict sense, has declined and been overcome by the so-called flexible management systems, mainly the Toyotist. However, there are as well investigations that show us that in the concrete reality of many companies, it is possible to find a combination of elements of these systems. In an effort to understand this apparently paradoxical picture, this article attempts to illuminate certain characteristics of the Taylorist, Fordist and Toyotist systems, intending to contribute to studies that analyze their possible hybridizations. We depart then, from a historical-materialist analysis, by which we conceive methods of exploitation of labour power suggested by these three systems – despite their peculiarities – as an integrating part of a more ample societal project, put in motion by private owners of means of production, which horizon is the formation of a restricted sociability, constrained by capital accumulation imperatives.